Municipal Regime - Quispe Correa, Alfredo (1981)
The objective of this paper is to analyze the regime of municipalities in the Political Constitution of Peru of 1979. To this end, a definition of municipality is developed, and its main characteristic components are described. To understand the most recent changes, a historical review of the modifications made up to the 1979 Constitution is made. In conclusion, it emphasizes the need to implement more changes in the municipalities' regime, to improve the organization of the State and to propose a more efficient model that properly responds to local and national needs.